A Comparative Analysis of the Aspects and Costs of Emergency Department Visits of Syrian Refugees with Turkish People and Former Refugees (Afghan People) - Tufan Alatlı (Journal of Contemporary Medicine, 2020)
Aim: Compare the emergency department (ED) use characteristics of old and new refugees and the local people and to investigate whether it brings a different financial burden on the economy of the country.